2019
DOI: 10.1097/prs.0000000000005624
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma and Platelet-Rich Fibrin Enhance the Outcomes of Fat Grafting: A Comparative Study

Abstract: Background: Autologous fat grafting is an efficient procedure in plastic surgery. However, its long-term tissue absorption is variable and technique-dependent. Platelet-rich plasma positively affects fat-grafting outcomes but still has shortcomings, and platelet-rich fibrin has been reported to have efficacy in fat transplantation. Here, we compared the effects of platelet-rich fibrin and platelet-rich plasma in fat grafting using histologic analysis. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 43 publications
0
22
0
1
Order By: Relevance
“…No presente relato de caso a utilização de L-PRF associado a um retalho vestibular sem interposição do corpo adiposo da bochecha resultou em regeneração óssea adequada e cicatrização saudável da mucosa, sem a ocorrência de complicações pós-operatórias. Portanto, essa técnica pode ser considerada viável e uma alternativa ao retalho pediculado com o corpo adiposo da bochecha, que apesar da ótima taxa de sucesso, pode resultar em alterações do contorno facial, hematoma e lesões nervosas, além de inviabilizar a possibilidade de sua utilização em uma eventual situação futura (Gheisari et al 2019;Nair et al 2019;Xiong et al 2019).…”
Section: Discussionunclassified
“…No presente relato de caso a utilização de L-PRF associado a um retalho vestibular sem interposição do corpo adiposo da bochecha resultou em regeneração óssea adequada e cicatrização saudável da mucosa, sem a ocorrência de complicações pós-operatórias. Portanto, essa técnica pode ser considerada viável e uma alternativa ao retalho pediculado com o corpo adiposo da bochecha, que apesar da ótima taxa de sucesso, pode resultar em alterações do contorno facial, hematoma e lesões nervosas, além de inviabilizar a possibilidade de sua utilização em uma eventual situação futura (Gheisari et al 2019;Nair et al 2019;Xiong et al 2019).…”
Section: Discussionunclassified
“…Activated platelets can release autogenous growth factors that may initiate signalling cascades and lead to multiple intracellular changes, promoting the proliferation, migration and differentiation of stem cells and regulating local inflammation and immune responses 5,6 . Due to its healing and regenerative properties, PRP has been widely applied in the aesthetic and dermatology fields, involving facial rejuvenation, androgenic alopecia enrichment, chronic hard‐to‐heal skin ulcers healing, acne scars improvement, fat grafting enrichment, vitiligo, and melisma treatment as well 7‐11 . Some studies also suggested that PRP could stimulate the proliferation of keratinocyte and fibroblasts, enhance interaction of keratinocyte and fibroblasts with melanocytes, and inhibit apoptosis of melanocytes 12‐14 .…”
Section: Introductionmentioning
confidence: 99%
“…Platelet-rich fibrin (PRF) is a second-generation platelet concentrate to replace platelet-rich plasma (PRP), and has become an attractive strategy in tissue grafting and regenerative medicine because it has abundant tissue healing-promoting cytokines and interleukins (ILs), including transforming growth factor beta 1 (TGF-β1), basic fibroblast growth factor (bFGF), platelet derived growth factor (PDGF), vascular endothelial growth factor (VEGF), IL-6, IL-8, IL-11, and so on (Masuki et al, 2016). Furthermore, PRF has been verified to increase tissue retention, quality, and neovascularized capillary density of grafted fat (Xiong et al, 2019). In addition, PRF has also been demonstrated to facilitate the regeneration of bone, periodontal tissue, and dental pulp (Chang and Zhao, 2011;Ji et al, 2015;You et al, 2019).…”
Section: Introductionmentioning
confidence: 99%